Sports participation, performance and medical-psychiatric health and illness: Cultural and religious effects - Ira D. Glick; Neil Eisenberg; Danielle Kamis (Hogrefe AG, 2023)
Abstract: Using one religion as an example, in the context of its historical culture, this article examines the medical and psychiatric literature on the role of religion and culture as it has affected sports. By way of providing background, we first review historical examples of how religion and its culture can affect sports participation, performance and psychiatric health/illness. Given these emotionally and religiously powerful influences over historical time, we then review implications for the sports physician or mental health therapist with a focus on how religious and cultural issues can affect diagnosis and treatment for athletes, their teams and communities. A case example is presented by way of illustrating the need to both be aware of religious-cultural negative and positive factors as they affect integrative treatment of athletes.